2011
DOI: 10.1111/j.1464-410x.2011.10050.x
|View full text |Cite
|
Sign up to set email alerts
|

Perinephric abscess

Abstract: The clinical condition of perinephric abscess can present dramatically as an acute emergency or insidiously as a chronic condition. The clinical characteristics and contemporary treatment approaches of these different types of perinephric abscess are outlined in this overview of the topic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
56
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 4 publications
0
56
0
1
Order By: Relevance
“…women was noted, while in previous studies, the male: Female ratio was reported as 1:31:7 [7,18,20] , and a female predominance as high as 91.8% was also observed [16] . Diagnosis of RA or PNA remains challenging because the symptoms can be insidious and obscure [1,2] . Patients with RA may present with fever, chills, flank or abdo minal pain, fatigue, nausea, decreased appetite, weight loss and even persistent hiccups [7,21,22] .…”
Section: Imaging Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…women was noted, while in previous studies, the male: Female ratio was reported as 1:31:7 [7,18,20] , and a female predominance as high as 91.8% was also observed [16] . Diagnosis of RA or PNA remains challenging because the symptoms can be insidious and obscure [1,2] . Patients with RA may present with fever, chills, flank or abdo minal pain, fatigue, nausea, decreased appetite, weight loss and even persistent hiccups [7,21,22] .…”
Section: Imaging Studiesmentioning
confidence: 99%
“…Perinephric abscess (PNA) is a collection of suppurative material located between Gerota's fascia and the renal capsule [2] . Complications of urinary tract infections (UTIs) and hematogenous seeding from primary infected sites are the common source of infection [2,3] .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations